Изучение механизмов реакций с тяжелыми ионами и получение вторичных радиоактивных пучков с помощью фрагмент-сепаратора КОМБАС. - Ю.Г, Тетерев (Scientific transaction of the National University of Mongolia. Physics, 2022)
Experiments in that Be and Ta targets have been bombarded by heavy ions in series 12C, 15N, 18O, 22Ne and 40Ar are discussed. Ions was accelerated at energy 35-45 MeV/nucleon on the U-400M cyclotron at Flerov Laboratory of Nuclear Reactions, JINK. The targets were placed at the entrance focus of the COMB AS separator. Reaction products near zero-angle degrees were collected and then analyzed. The telescope formed from silicon detectors was placed at the exit achromatic focus of separator. One from pair of parallel plate avalanche counters (PPAC) has been placed at the dispersive focal plane and the other before the silicon detectors. Reaction products was identified on the mass number A and atomic number Z by the (ДЕ. K) telescope and by the (AE. T) method using lime of flight between PPAC. The measurements of the yields of isotopes were carried out by scanning the range of magnetic rigidities covering the velocity distributions of the studied isotopes. The results of the experiments was analyzed and compared with different theoretical models. The generation of radioactive beam of 11Li with maximum intensity and its purity was the objective of this experiment. Achieved maximum intensity is 104 nuclei at second.